Empowering Islamic Boarding School Students with an Introductory IELTS Program - Fadhlur Rahman; Salmina Elvia Amanda; Chadtrun Nada (PT FORMOSA CENDEKIA GLOBAL, 2023)
A command of the English language is required for students to pursue higher education abroad, particularly in the context of the International English Language Testing System (IELTS). Through a community service program, this study aims to introduce Islamic Boarding School students to IELTS. The training program, a collaboration between the State Islamic Institute of Lhokseumawe and Integrated Dayah Al-Muslimun (one of the top-tier Islamic Boarding Schools in North Aceh), aimed to improve the English language skills of community service participants. The training program was enthusiastically attended by community service participants (students), demonstrating their desire to improve their language skills and prepare for future academic endeavors. With IELTS certificates required for new student admissions at international universities, this collaborative training initiative is critical for empowering Islamic Boarding School students to successfully pursue educational opportunities abroad. This program aims to promote participants' academic and professional development on a global scale by providing them with the necessary language skills.